2010
DOI: 10.1086/651135
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages Can Treat and PreventPseudomonas aeruginosaLung Infections

Abstract: Antibiotic-resistant bacteria threaten life worldwide. Although new antibiotics are scarce, the use of bacteriophages, viruses that infect bacteria, is rarely proposed as a means of offsetting this shortage. Doubt also remains widespread about the efficacy of phage therapy despite recent encouraging results. Using a bioluminescent Pseudomonas aeruginosa strain, we monitored and quantified the efficacy of a bacteriophage treatment in mice during acute lung infection. Bacteriophage treatment not only was effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
274
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 274 publications
(293 citation statements)
references
References 34 publications
(37 reference statements)
10
274
1
4
Order By: Relevance
“…Alterations of these physical parameters are known to occur in diseased mucosal surfaces [e.g., the high mucin concentrations (>4% wt/vol) and acidified mucosa characteristic of cystic fibrosis] (40,44). Although numerous studies have documented the effective use of phages to treat cystic fibrosis-associated bacterial infections (45,46), how physical and physiological changes in the lung might affect phage diffusion, the frequency of productive phage-host encounters, and bacterial infection dynamics remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of these physical parameters are known to occur in diseased mucosal surfaces [e.g., the high mucin concentrations (>4% wt/vol) and acidified mucosa characteristic of cystic fibrosis] (40,44). Although numerous studies have documented the effective use of phages to treat cystic fibrosis-associated bacterial infections (45,46), how physical and physiological changes in the lung might affect phage diffusion, the frequency of productive phage-host encounters, and bacterial infection dynamics remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Besides rapid coevolution, further complications could arise from interspecific bacterial competition due to polymicrobial nature of bacterial infections: many human infections contain multiple different pathogenic bacterial and other microbial species (Peters, Jabra‐Rizk, O'May, Costerton, & Shirtliff, 2012). Considerable genotypic variation also exists between different strains of a pathogen, and this variation is known to differ between different patients and to affect the pathogen susceptibility to phages (Debarbieux et al., 2010; Essoh et al., 2013; Friman, Ghoul, Molin, Johansen, & Buckling, 2013). Understanding the relative importance and interactive effects of these potentially complicating factors is thus crucial for developing reliable and consistent phage therapy treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Several animal studies have demonstrated the efficacy and safety of phage therapy in the treatment of different infections [29][30][31]. In humans, potential applications of phages include the phage-mediated prevention and phage treatment expanding from conventional phage therapy, treatment with phage enzymes (e.g.…”
Section: B) Phage Therapy (Including Derivatives)mentioning
confidence: 99%